Cournot's model applied to cellphone service in Colombia, 1995-2001 (2006)
Purpose - The purpose of this paper is to develop and empirically test the conditions that describe adjustment velocities to reach equilibrium under Cournot's duopoly model. Design/methodology/approach - The paper uses a vector error correction (VEC) framework as the basis for determining and testing adjustment velocities using data about cellphone service in Colombia in the time period from 1995 to 2001. Findings - Empirical evidence suggests the following: first of all, companies operating in the cellphone market behave as cournot's competitors and have constant marginal costs; secondly, cellphone companies operating in the eastern zone of Colombia are in long-term equilibrium; and lastly, equilibrium adjustment velocities are statistically significant. As predicted by theory, in terms of welfare, the existence of equilibrium in Cournot's model implies that cellphone users in the eastern zone of Colombia enjoy a small consumer surplus. Originality/value - Testing the microeconomic implications of the equilibrium dynamics of Cournot's model, using a VEC framework. © Emerald Group Publishing Limited.